2020
DOI: 10.1177/0738894220906370
|View full text |Cite
|
Sign up to set email alerts
|

Politics of interconfessional empathy and Schadenfreude in Lebanon

Abstract: We analyze the sources of two politically relevant, yet opposing emotions: empathy and Schadenfreude. We propose that group and individual-level political factors affect empathy and Schadenfreude toward other groups. Using a survey experiment conducted in Lebanon we find that, when presented with a prompt about political repression, respondents are less likely to express empathy and more likely to express Schadenfreude when victims of political repression were from the out-group perceived as their group’s most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Indeed, Webster and colleagues (2021) show that a sizable portion of Americans engage in partisan schadenfreude such that they express joy (not concern) when unfortunate events befall those with whom they disagree politically. Similar findings have been reported regarding political schadenfreude and sympathy in Lebanon (Ash & Dolan, 2021). Combs and colleagues (2009) also showed that the intensity of schadenfreude individuals express following hypothetical misfortunes of political leaders is directly related to political party affiliation (controlling for sympathy), such that the misfortune of a Democratic figurehead (out-group member) sparks high levels of schadenfreude in Republicans but not Democrats (and vice versa).…”
Section: Schadenfreude and Sympathy In Political Contextssupporting
confidence: 65%
“…Indeed, Webster and colleagues (2021) show that a sizable portion of Americans engage in partisan schadenfreude such that they express joy (not concern) when unfortunate events befall those with whom they disagree politically. Similar findings have been reported regarding political schadenfreude and sympathy in Lebanon (Ash & Dolan, 2021). Combs and colleagues (2009) also showed that the intensity of schadenfreude individuals express following hypothetical misfortunes of political leaders is directly related to political party affiliation (controlling for sympathy), such that the misfortune of a Democratic figurehead (out-group member) sparks high levels of schadenfreude in Republicans but not Democrats (and vice versa).…”
Section: Schadenfreude and Sympathy In Political Contextssupporting
confidence: 65%
“…As another example, people are less likely to feel empathy and more likely to feel schadenfreude in the face of political repression when the group being repressed is a member of an outgroup rather than an ingroup. The extent of political repression can severe, such as a group peacefully protesting getting killed by the state's army (Ash & Dolan, 2020). The lack of empathy and the increase in schadenfreude makes collective action on behalf of the rival group less likely to occur (Stefaniak et al, 2020), increasing the inequality between political groups in line with ingroup political interests.…”
Section: The Power Of Empathy and Counter-empathy To Enhance Hierarchymentioning
confidence: 99%
“…Lebanon as a state is composed of several confessions (approximately eighteen religious' communities) (Henley, 2016;Author, 2019;Majed, 2020). The political system in Lebanon is constructed as the confessional system meaning political power is distributed among the Lebanese communities according to their percentage of the population (Harb, 2006;Calfat, 2018;Ash & Dolan, 2021). The president of Lebanon is a Christian Maronite, the prime minister is a Muslim Sunni, and the speaker of the Parliament is a Muslim Shia (Naor, 2013).…”
Section: Lebanese Sunni Muslims' Narratives On the Political And Reli...mentioning
confidence: 99%
“…This enables them to constitute an integral part of Lebanon's confessional political system which specifies that the Lebanese president should be a Christian Maronite, the prime minister a Muslim Sunni and the speaker of parliament a Muslim Shia (Lust, 2011;Najem, 2012;Salloukh et al, 2015). Therefore, the confessional system in Lebanon, despite its flaws, has provided opportunities for the Sunnis to hold the position of the prime minister and other key positions in the Lebanese government (Ash & Dolan, 2021;Badran, 2021;Meier and Di Peri, 2017).…”
Section: Introductionmentioning
confidence: 99%